DNA Computing and Molecular Programming 19th International Conference, DNA 2013, Tempe, AZ, USA, September 22-27, 2013, Proceedings - Soloveichik, David; Yurke, Bernard (Theoretical Computer Science and General Issues, 2013)
This book constitutes the refereed proceedings of the 19th International Conference on DNA Computing and Molecular Programming, DNA 19, held in Tempe, AZ, USA, in September 2013. The 14 full papers presented were carefully selected from 29 submissions. The papers are organized in many disciplines (including mathematics, computer science, physics, chemistry, material science and biology) to address the analysis, design, and synthesis of information-based molecular systems.